OPTIMAL HEATING RATE IN THERMAL SENSITIVE BODIES BY RESTRICTIONS ON ENVIRONMENT TEMPERATURE AND ON PLASTIC STRAINS - Кушнір, Роман Михайлович; Ясінський, Анатолій Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this talk, the mathematical formulation and a solution algorithm for one-dimensional optimal speed-processing-control problem of heating thermo-sensitive bodies of the canonical shape is presented. A control function (the temperature of surrounding contacting with a part of the limiting surface, or the heat flux) is determined for transmitting the body from an initial thermal state into a required final one, which is characterized by an integral-average temperature, in the minimum time under constrains for both the control function and the maxim value of accumulated plastic shear-deformation.